Pemanfaatan Prinsip Kerja Sama Dalam Komunikasi Diskusi Sebagai Aspek Keterampilan Berbicara Mata Pelajaran Bahasa Indonesia Kelas 8 Di SMP Muhammadiyah 4 Surakarta - Ayu Tri Cahya Mulati, Mega, Prof. Dr. H. Abdul NgalimM.M., M.Hum (2016)
ABSTRACT Mega Ayu Tri Cahya Mulati. A310120169. Utilization of Principle of Cooperation in Communication Discussion As aspect Speaking Skills Indonesian Lesson Class 8 In SMP Muhammadiyah 4 Surakarta. Essay. The Faculty of Education, University of Muhammadiyah Surakarta. June, 2016. Discussions included in one of the methods used by the teacher in the learning process, especially Indonesian. Discussion method can train students in speaking skills. Speaking skills is one aspect that must be owned by the students. A student who has had speaking skills will be easy to follow the discussion. Connection with speaking skills, students must apply the principles of cooperation. The purpose of this study is to describe the shape of the principle of cooperation and utilization used by teachers and students in discussion. This type of research is qualitative. The data used in this study is the communication that occurs between teachers and students during the learning process (discussions). Researchers used a technique refer to records in data collection. Based on the data that has been studied, showed that the use of the principles of cooperation in every speech of teachers and students. The principle of such cooperation include the use maxim of quantity, quality, relevance, and execution. Utilization principles of cooperation has shown that students have developed speaking skills. Speech between students and teachers have demonstrated their understanding of the meaning accepted by the hearer and the speaker. Keywords: discussion, speaking skills, principles of cooperation.